A Multi-Oscillatory Circadian System Times Female Reproduction - Simonneaux, Valérie; Bahougne, Thibault (Frontiers in Endocrinology, 2015)
Rhythms in female reproduction are critical to insure that timing of ovulation coincides with oocyte maturation and optimal sexual arousal. This fine tuning of female reproduction involves both the estradiol feedback as an indicator of oocyte maturation, and the master circadian clock of the suprachiasmatic nuclei as an indicator of the time of the day. Herein we are providing an overview of the state of knowledge regarding the differential inhibitory and stimulatory effects of estradiol at different stages of the reproductive axis, and the mechanisms through which the two main neurotransmitters of the suprachiasmatic nucleus, arginine vasopressin and vasoactive intestinal peptide, convey daily time cues to the reproductive axis. In addition we will report the most recent findings on the putative functions of peripheral clocks located throughout the reproductive axis (kisspeptin neurons, GnRH neurons, gonadotropic cells, the ovary and the uterus). This review will point to the critical position of the kisspeptin neurons of the anteroventral periventricular nucleus, which integrate both the stimulatory estradiol signal, and the daily arginine vasopressinergic signal, while displaying a circadian clock. Finally, given the critical role of the light/dark cycle in the synchronization of female reproduction, we will discuss the impact of circadian disruptions observed during shift work conditions on female reproductive performance and fertility in both animal model and humans.